2014
DOI: 10.1590/0103-6440201300037
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Interfacial Adaptation of Root Canal Sealers

Abstract: This study compared the physicochemical properties and interfacial adaptation to canal walls of Endo-CPM-Sealer, Sealapex and Activ GP with the well-established AH Plus sealer. The following analyses were performed: radiopacity, pH variation and solubility using samples of each material and scanning electron microscopy of root-filled bovine incisors to evaluate the interfacial adaptation. Data were analyzed by the parametric and no-parametric tests (α=0.05). All materials were in accordance with the ANSI/ADA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1
11

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 23 publications
2
25
1
11
Order By: Relevance
“…Other studies showed no direct correlation between smear layer removal and root canal sealer penetration, as there was no significant difference between apical, middle and coronal portions of the tested specimens [36,37]. In our study, such differences may be due to the improved physico-chemical properties and flowability of the chosen root canal sealer [38].…”
Section: Discussioncontrasting
confidence: 53%
“…Other studies showed no direct correlation between smear layer removal and root canal sealer penetration, as there was no significant difference between apical, middle and coronal portions of the tested specimens [36,37]. In our study, such differences may be due to the improved physico-chemical properties and flowability of the chosen root canal sealer [38].…”
Section: Discussioncontrasting
confidence: 53%
“…The small solubility of AH Plus sealer would contribute for the antibacterial action and local repair [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…[5] evaluated the physicochemical properties, radiopacity, pH, and solubility of Endo CPM Sealer, Activ GP, and Sealapex, compared with those of AH Plus sealers. Concerning to the solubility, all materials meeting the requirements of ANSI/ADA, that is, solubility lower than 3% of the weight, without statistically significant differences among the sealers.…”
Section: Solubilitymentioning
confidence: 99%
“…AH Plus has demonstrated low solubility and good dimensional stability in solutions. It can adhere to root dentin due to its creep properties and long setting times [13,19,20]. Regarding the antimicrobial properties, epoxy-resin based sealers have shown to produce some antibacterial properties but mainly before their setting due to the release of some of the constituents like formaldehyde [21,22].…”
mentioning
confidence: 99%